Immunological responses to adjuvant vaccination with combined CD1c+ myeloid and plasmacytoid dendritic cells in stage III melanoma patients. (1st January 2022) - Bloemendal, Martine; Bol, Kalijn F.; Boudewijns, Steve; Gorris, Mark A.J.; de Wilt, Johannes H.W.; Croockewit, Sandra A.J.; van Rossum, Michelle M.; de Goede, Anna L.; Petry, Katja; Koornstra, Rutger H.T.; Figdor, Carl; Gerritsen, Winald R.; et al.
ABSTRACT: We evaluated the immunological responses of lymph-node involved (stage III) melanoma patients to adjuvant dendritic cell vaccination with subsets of naturally occurring dendritic cells (nDCs). Fifteen patients with completely resected stage III melanoma were randomized to receive adjuvant dendritic cell vaccination with CD1c + myeloid dendritic cells (cDC2s), plasmacytoid dendritic cells (pDCs) or the combination. Immunological response was the primary endpoint and secondary endpoints included safety and survival. In 80% of the patients, antigen-specific CD8 + T cells were detected in skin test-derived T cells and in 55% of patients, antigen-specific CD8 + T cells were detectable in peripheral blood. Functional interferon-γ-producing T cells were found in the skin test of 64% of the patients. Production of nDC vaccines meeting release criteria was feasible for all patients. Vaccination only induced grade 1–2 adverse events, mainly consisting of fatigue. In conclusion, adjuvant dendritic cell vaccination with cDC2s and/or pDCs is feasible, safe and induced immunological responses in the majority of stage III melanoma patients.